Mengaggas Program Pengembangan Keberagamaan Peserta Didik - Nurul Fadhilah (Permata : Jurnal Pendidikan Agama Islam, 2022)
This study describes the development program of the diversity of learners. Background of the study, due to the learning process of Islamic religious education (PAI) in the school have the short or narrow, that only about 4JP (4X35 minutes). So, the purpose of religious education it's difficult to be achieved if only rely on the PAI learning in school.This study uses a type of research literature review. Research literature review or literature review and literature research, a research that assess or review critically the knowledge, ideas, or findings contained in a body of literature-oriented academic-oriented literature. While the data sources of this study, using two data sources, namely primary data source of literature about the program is the diversity of learners, and secondary data sources, namely the supporting data which has the relevance of the data as well as provide research information about the program is the diversity of learners. While the technique of data analysis using data analysis techniques descriptive interpretative.The results showed that the program of development of the diversity of learners in the primary school level can be implemented in the form of a program habituation routine and program habituation incidental. While program development the diversity of learners at the level of SMP/MTs can be implemented in the form of a program intrakulikuler and cca programs. Programs are designed and conducted has become imperative to adjust with the growth or development of intelligence psychological learners, and adjust with the potential in the talent and interest of the learners.Keyword: Program Development; Diversity; Learners. Abstrak Penelitian ini mendeskripsikan tentang program pengembangan keberagamaan peserta didik. Latar belakang kajiannya, disebabkan karena proses pembelajaran pendidikan agama Islam (PAI) di sekolah memiliki waktu yang pendek atau sempit, yang hanya berkisar 4JP (4X35 menit). Sehingga, tujuan pendidikan keagamaan sulit rasanya untuk dicapai apabila hanya mengandalkan pembelajaran PAI di sekolah.Penelitian ini menggunakan jenis penelitian literature review. Penelitian kepustakaan atau kajian literature review and literature research, merupakan penelitian yang mengkaji atau meninjau secara kritis akan pengetahuan, gagasan, atau temuan yang terdapat di dalam tubuh kepustakaan yang berorientasi academic oriented literature. Sementara sumber data penelitian ini, menggunakan dua sumber data yaitu sumber data primer kepustakaan mengenai program keberagamaan peserta didik, dan sumber data sekunder, yakni data-data penunjang yang memiliki relevansi data serta memberikan informasi penelitian tentang program keberagamaan peserta didik. Sedangkan teknik analisis data menggunakan teknik analisis data deskriptif interpretatif.Hasil penelitian menunjukan bahwa program pengembangan keberagamaan peserta didik di tingkat SD/MI dapat dilaksanakan dalam bentuk program pembiasaan rutin dan program pembiasaan insidental. Sementara, program pengembangan keberagamaan peserta didik di tingkat SMP/MTs dapat dilaksanakan dalam bentuk program intrakulikuler dan program ekstrakulikuler. Program-program yang dirancang dan dilaksankan sudah menjadi keharusan untuk menyesuaikan dengan pertumbuhan atau perkembangan kecerdasan psikologis peserta didik, dan menyesuaikan dengan potensi pada bakat minat peserta didik.Kata Kunci: Program Pengembangan; Keberagamaan; Peserta Didik.